Readiness for shared services in higher learning institution: A pilot study - Jais J.; Naidu P.; Asshidin N.H.N.; Yusof M. (Institute of Medico-Legal Publications, 2023)
article; human; job satisfaction; learning; Malaysia; organization; pilot study; quantitative analysis; work engagement